Description of the larva of Planiplax sanguiniventris (Calvert, 1907) (Odonata: Libellulidae) - Novelo-Gutiérrez, Rodolfo (Zootaxa, 2021)
The last instar larva of Planiplax sanguiniventris (Calvert, 1907) is described and illustrated in detail based on one specimen collected in the municipality of Tenosique, Tabasco, Mexico. It is compared with the larvae of P. phoenicura Ris, 1912 and a congeneric unidentified species from Colombia. The main structural features are the number of setae on palp and prementum, the size of dorsal protuberance on S3, and the length of posterolateral spines on S8–9 and caudal appendages.